A Cognitive Bias for Zipfian Distributions? Uniform Distributions Become More Skewed via Cultural Transmission. Issue 1 (9th July 2022) - Shufaniya, Amir; Arnon, Inbal
Abstract: There is growing evidence that cognitive biases play a role in shaping language structure. Here, we ask whether such biases could contribute to the propensity of Zipfian word-frequency distributions in language, one of the striking commonalities between languages. Recent theoretical accounts and experimental findings suggest that such distributions provide a facilitative environment for word learning and segmentation. However, it remains unclear whether the advantage found in the laboratory reflects prior linguistic experience with such distributions or a cognitive preference for them. To explore this, we used an iterated learning paradigm—which can be used to reveal weak individual biases that are amplified overtime—to see if learners change a uniform input distribution to make it more skewed via cultural transmission. In the first study, we show that speakers are biased to produce skewed word distributions in telling a novel story. In the second study, we ask if this bias leads to a shift from uniform distributions towards more skewed ones using an iterated learning design. We exposed the first learner to a story where six nonce words appeared equally often, and asked them to re-tell it. Their output served as input for the next learner, and so on for a chain of ten learners (or 'generations'). Over time, word distributions became more skewed (as measured by lower levels of word entropy). The third study asked if the shift will be less pronounced when lexical access was made easier (by reminding participants of the novel word forms), but this did not have a significant effect on entropy reduction. These findings are consistent with a cognitive bias for skewed distributions that gets amplified over time and support the role of entropy minimization in the emergence of Zipfian distributions.